PENGARUH KOMBINASI FITOHORMON DAN ZAT PENGATUR TUMBUH (ZPT) UNTUK MENINGKATKAN PERTUMBUHAN Chlorella sp. - Erlangga Erlangga; Zulfikar Zulfikar; Muhammad Anggi (Berkala Perikanan Terubuk, 2018)
This study aims to determine the dosage of phytohormone and the appropriate growth regulator in Chlorella sp culture to increase the growth of Chlorella sp.The method used in this study was the experimental method with fitohormon as a factor A which were cytokines (0,02 gr/l), auksin (0,065 gr/l) and the growth regulator (PGR) as a factor B which were TSP (0,03 gr/l), NPK (0,04 gr/l). the treatment would be undertaken for the treatment of hormone auxin A (0,065 gr/l) anf TSP (0,03 gr/l) B.The result is the hormone cytokinins (0,02 gr/l) and NPK (0,04 gr/l) the highest growth of Chlorella sp cells was in the treatment D cytokinins (0,02 gr/l) and NPK (0,04 gr/l), then it was followed by treatment B hormone auxin (0,065 gr/l) and NPK (0,04 gr/l), C hormone cytokinins (0,02 gr/l) and TSP (0,03 gr/l) and A auxin (0,065 gr/l) anf TSP (0,03 gr/l). population peak of chlorella cell in each treatment were : D D (2041.67 x 103 sel/ml), B (1610.67 x 103 sel/ml), C (1592.67 x 103 sel/ml), treatment A showed the lowest value which was (1589.33 x 103 sel/ml). water quality parameters strongly supported theprocess of cell proliferation or growth of Chlorella sp with pH 7.0-7.3, salinity 27-30 ppt, and temperature of 22.4-25 0C.